FieldFresh Foods : could baby corn be the platform to link Indian farmers to the world? - Pandey, Mukesh, 1970-; Sudhir, K.; Ahuja, Raman; Tewari, Deepali ([London] : SAGE, 2016)
On one of those pleasant cold February mornings, Sanjay Nandrajog, the CEO of FieldFresh Foods Private Limited, pondered the future. He had just returned to Delhi from the company's Agri Centre of Excellence (ACE), an R&D farm where he celebrated the dispatch of 500 metric tons of fresh baby corn to Europe. The top management team at FieldFresh was justifiably proud of this achievement as it had required tremendous effort to become an important exporter of Indian produce. FieldFresh had been incorporated in 2004 with the vision of linking Indian fields to the world. India had a number of natural advantages in terms of climate, acres in production, and labour force to become a major power in agriculture. This case study examines this topic.
Originally Published in: Pandey, M., Sudhir, K., Ahuja, R., & Tewari, D. (2010). FieldFresh Foods: Could Baby Corn Be the Platform to Link Indian Farmers to the World? 10-036. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; FieldFresh Foods (Firm); Production management -- Case studies; Strategic planning -- Case studies